Cognitive performance of elder people participating in elder´s organized groups in San José - Castro, María (2014)
Since cognitive performance is a major determinant for the development of healthy aging processes and quality of life, the profiles of cognitive performance in executive functions and memory of 110 elders participating in organized groupsin Costa Rica were described. Sociodemographic data were registered, and variables of cognitive performance and level of involvement in activities were evaluated. Participant showed a cognitive performance expected for their age and educational level in screening tests for global intellectual performance whereas in tests assessing executive functioning and memory performance showed a normatively expected score; however, it was located in the middle and lower ranks. Although the participants did not show a high level of cognitive performance, they have an active lifestyle with a variety of formal activities and social participation.